Reliability, Neighborhood Discovery and Active Node Selection in Wireless Sensor Networks - Bhargavi Mopuru; M Naga Bhushana Rao (Journal of Networking Technology, 2018)
In the present computer world Wireless Sensor Networks are playing a major role in sensing environment, health care and embedded systems category. In WSNs sensors are the nodes which are deployed randomly and in a wide spread manner. Data can be transmitted to the controller by the sensors at periodic intervals. As the network is dynamic the number and behavior of nodes vary randomly and identifies the nodes which are active are selected and the nodes which are idle are neglected. In WSN, the topology of the network is dynamic, it is necessary to identify the neighbors in the proximity and coordinate data acquisition at the controller. In any network reliability is an important issue which deals with stability under mobility, low delay, more life time, optimal route and other optimizations.